The use of enzymatically synthesized medium- and long-chain triacylglycerols (MLCT) oil blends in food application - Koh S.P.; Long K.; Tan C.P.; Yusoff M.S.A.; Lai O.M.; Arifin N. (2024)
Indexed by Scopus